AN ANALYSIS OF TEACHER ROLE IN TRAINING CHILDREN’S DISIPLINE THROUGH CONGREGATIONAL PRAYER PRACTICE IN GROUP B2 SAVE THE KIDS KINDERGARTEN BANDA ACEH - Dewi Yunisari; Elvina; Musdiani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Discipline is a process of guidance that has the aim of instilling certain patterns of behavior and certain habits. Actually discipline is getting children to obey the rules in their environment. The research objectives are 1. To describe the activities carried out in training the development of early childhood discipline in the Save The Kids Kindergarten Banda Aceh. 2. Knowing the obstacles faced by teachers in teaching the development of early childhood discipline in B2 Kindergarten Save The Kids Banda Aceh. 2. Knowing the teacher's role in training the discipline of congregational prayer for early childhood in the B2 group of Save The Kids Kindergarten Banda Aceh.?. In this study, a descriptive qualitative design was chosen. Qualitative descriptive is research conducted with the aim of making a picture or description of a situation objectively by using interview instruments addressed to 3 teachers as respondents. The results showed that: 1. In general, the teacher's role in training disciplined learning in the practice of praying together went well, so that this supported children's success in exploring their activities which caused generally children's education to develop well. 2. The teacher provides motivation and tells stories so that the child's discipline develops well in the practice of praying together. 3. The teacher pays special attention to every child whose discipline development is lacking, namely by giving special attention to the child.